CMLHS 2010 Appreciation Night - Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
13 December 2010. CMLHS Appreciation Night is an annual event to honour all work, contributions and dedication of CMLHS associates. For 2010, MS Garden Hotel, Kuantan took its turn to witness the esteemed event where those who were excellent in their services were honoured according to seven categories.